Optimal policy towards families with different amounts of social capital, in the presence of asymmetric information and stochastic fertility - Alessandro Cigno; Annalisa Luporini (Center for Economic Studies and ifo Institute (CESifo), 2006)
We examine the effects of differences in social capital on first and second best transfers to families with children, in an asymmetric information context where the number of births, and the future earning capacity of each child that is born, are random variables. The probability that a couple has children is conditional on the level of reproductive activity undertaken. The probability that a child will have high earning ability is positively conditioned not only by the level of educational investment undertaken by the child's parents, but also by the social capital of the latter. The optimal policy includes two transfers, one conditional on number of births, the other on the children's earning ability.
Keywords: D13; D82; D78; J13; H31; 330; education; stochastic fertility; child benefits; pensions; scholarships; social capital; asymmetric information; multi-agency; Familienleistungsausgleich; Familienpolitik; Social Capital; Bildungsinvestition; Fruchtbarkeit; Asymmetrische Information; Humankapital; Theorie